CFD and MRI studies of hemodynamic changes after flow diverter implantation in a patient-specific model of the cerebral artery - Frolov, S. V. (2018)
Abstract: Flow changes after flow diverter (FD) placement may be assessed by 4D phase-contrast MR-angiography (4D flow MRI) or simulated by computational fluid dynamics (CFD). However, cross-validation and future assessments with both approaches to take advantage of their individual strengths are required. In this study, we investigate the influence of a FD on intra-aneurysmal blood flow using both MRI experiments and CFD simulations. MR measurements were performed in a true-to-scale silicone model of a wide-neck saccular aneurysm of the distal internal carotid artery before and after FD deployment. An experimental setup, including a computer-controlled piston pump, was assembled to simulate pulsatile blood flow. For CFD studies, a virtual stenting technique was used to place a FD into the aneurysm model. Boundary conditions were applied according to MRI-measured flow data. A qualitative and quantitative agreement of velocity fields measured by CFD and MRI both before and after FD placement was demonstrated. The intra-aneurysmal flow reduction in the CFD results was 19%, while a reduction of 23% was measured by 4D flow MRI. Despite of the low spatial resolution, MRI was able to correctly determine the flow pattern in the aneurysm. The pre-treatment CFD simulation could be helpful in predicting the outcome of a FD treatment, while a post-interventional MRI could prove the desired treatment effect.